Selection of the transplant for myocardial revascularization - G. G. Khubulava; A. S. Nemkov; V. V. Komok; Yi. Chzan (Вестник хирургии имени И.И. Грекова)
Surgical treatment of coronary heart disease was introduced into clinical practice more than 50 years ago. Only one intervention – the use of left internal thoracic artery for bypass grafting of the anterior interventricular artery – Kolovos’s operation– remains practically unchangeable version of execution as a standard for coronary artery bypass grafting. This review summarizes the half-century use of internal thoracic arteries, autoveins, radiate arteries as conduits for coronary arteries on the basis of the randomized studies and meta-analyzes published by 2018.